Філософія й естетика вітчизняного літературного імпресіонізму: європейські джерела, українська генеза, радянський розгром - Ямчук, Павло; Yamchuk, Pavlo (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті розглянуто європейські джерела, українську генезу та штучне радянське придушення філософії й естетики українського літературного імпресіонізму. Досліджено провідні концепти вітчизняної імпресіоніс-тичної творчості в загальноєвропейському контексті, проведено паралелі з втіленнями імпресіонізму в дискур-сах інших європейських культур. The article deals with European sources, Ukrainian Soviet genesis and artificial suppression of philosophy and aesthetics Ukrainian literary impressionism 1890−1930-ies. Explores the concepts of domestic leading Impressionist art in the European context, drawing parallels with the embodiments of Impressionism in the discourses of other European cultures. Separately drawn attention to the complexity of the formation of Ukrainian impressionist philosophy and aesthetics in a pivotal era in the cultural life of Ukraine and Europe as a whole (the emergence of modernism and its diverse stylistic trends and literary and artistic movements), and socio-historical era of the Ukrainian state, and then − its artificial destruction and suppression. The examples impressionistic literary creativity is analyzed deep interrelation of processes of socio-cultural and national Ukrainian Executed Renaissance, which took place in Ukraine in late XIX − early XX centuries.
Philosophy and Aesthetics of Domestic Literary Impressionism: European Sources, the Genesis of Ukrainian Soviet Defeat.
Keywords: імпресіонізм; impressionism; філософія; philosophy; літературознавство; aesthetics; українознавство; Ukrainian studies; мистецтвознавство; art history